Study Effect of Performance Wind Turbines on the Performance of DcAc Converter for Dc Motor Application Using Fuzzy Logic Control - suliman, khaled; Ahteewish, Aymen; Baghni, Mohamed (Sharwes Scientific Journal, 2025)
Generation of electricity from wind power has received considerable attention because it isplentiful, renewable, produces no greenhouse gas emissions during operation and uses little land Inorder to meet the fast dynamic response requirement of the three phase voltage resource rectifiersystem, this paper designed a voltage fuzzy logic voltage controller with the direct busbar voltageerror and the slope of the error based on the theory of fuzzy logic control, and got the parameters ofthe fuzzy logic controller. A simulation model was created in Matlab. The overshoot of the systemresponse and time of system dynamic response were compared with the experiments of traditionalPI controller versus Fuzzy controller based on Matlab-Simulink platform during the operationincluding starting, increasing load and decreasing load. From the simulation results, this controlstrategy could improve the dynamic and static performance of the system with the waves of Matlabsimulation model, not changing the topology of the system without obviously addingimplementation burden of fuzzy controller.